Synthesis of ethyl acetate by dehydrogenation of ethanol. Process study. Technological aspects - I. P. Semenov; Yu. A. Pisarenko; V. A. Menshchikov (Тонкие химические технологии)
Experimental data of a study on the synthesis of ethyl acetate by catalytic dehydrogenation of ethanol are presented. Tests of the catalyst were carried out in a flow reactor at a temperature of 230–300 ° С and under a pressure of 0.1–2.0 MPa. Industrial catalyst NTK-4 was used. Conversion of ethanol was 40–63%, selectivity was 86–94%. In the process hydrogen is produced, and it can be used on one of the stages of the process. Some technological aspects are also presented.